The Effect of OCB Organizational Citizenship Behavior and Work Discipline on Organizational Commitment in Mediation with Job Satisfaction at Bank Indonesia Representative Office in North Sumatra Province - Azaria Tarigan; Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
The support of facilities and infrastructure as well as adequate sources of funds are other important elements in moving the wheels of the organization, but without the support of reliable human resources, organizational activities will not run, so that the optimization of the achievement of organizational goals is impossible to achieve. This condition indicates that human resource development is an inevitable demand to ensure the availability of quality human resources according to the demands of the organization. The results of this study are as follows: Discipline has a positive and significant effect on Job Satisfaction with a value of 0.353 and a significant value of 0.012. Work Discipline had a positive and insignificant effect on Organizational Commitment with a value of 0.090 and a significant 0.323. Job Satisfaction had a positive and significant effect on Organizational Commitment with a value of 0.745 and a significant 0.000. Organizational Citizenship Behavior had a positive and significant effect on Job Satisfaction with a value of 0.557 and a significant 0.000. Organizational Citizenship Behavior had a positive and insignificant effect on Organizational Commitment with a value of 0.070 and a significant 0.301. Work Discipline had a positive and significant effect on Organizational Commitment through Job Satisfaction with a value of 0.263 and a significant score of 0.008. Organizational Citizenship Behavior has a positive and significant effect on Organizational Commitment through Job Satisfaction with a value of 0.415 and a significant value of 0.004.